WATER BALANCE DAS KAITI SAMO KECAMATAN RAMBAH - Rismalinda - (Jurnal APTEK, 2013)
The purpose of this study was to determine the balance between water availabilityin particular water needs in agriculture (rice water availability) using Gambel method for rainfall, FJ method Mockforriver flow based on rain fall.For water needs using evapotranspiration values (ETo) based on climatological data including air temperature (temperature), wind speed, solar radiation and humidity old at Rambah rain fall station from 2002 to 2011. By using the method Pennmant.The results of this study demonstrate that for 50 years and then water shed Kaiti Samo still in good shape when cared for properly.